2020
DOI: 10.1177/0886260520960302
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Romantic Partnership Dynamics in Domestic Minor Sex Trafficking Case Files

Abstract: Domestic minor sex trafficking (DMST) is the commercial sexual exploitation of a minor citizen or legal resident within the United States. Previous research suggests that although DMST is often discussed as though it is a uniform phenomenon, traffickers may use different tactics and exploit different victim vulnerabilities depending upon their established relationships with those who are at-risk for trafficking. The purpose of this qualitative study, therefore, is to explore the relationship patterns and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In examining dynamics of DMST cases, Twis et al (2020) highlighted the similarities found between the context and dynamics of the DMST violence and the dynamics known to exist in adolescent IPV or teen dating violence situations. The findings presented here linking DMST and community violence, along with the noted similarities between trafficker-inflicted violence and adolescent partner violence, emphasizes the need to integrate DMST prevention efforts in advocacy and programing that target community violence and/or IPV in adolescence (Twis, 2020;Twis et al, 2020). Recognizing the intersection of DMST and adolescent interpersonal violence, future DMST prevention and intervention strategies focused on education should provide messaging and resources for violence beyond DMST, while screening and/or service provisions for adolescents should ask about and incorporate resources for interpersonal violence along with DMST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In examining dynamics of DMST cases, Twis et al (2020) highlighted the similarities found between the context and dynamics of the DMST violence and the dynamics known to exist in adolescent IPV or teen dating violence situations. The findings presented here linking DMST and community violence, along with the noted similarities between trafficker-inflicted violence and adolescent partner violence, emphasizes the need to integrate DMST prevention efforts in advocacy and programing that target community violence and/or IPV in adolescence (Twis, 2020;Twis et al, 2020). Recognizing the intersection of DMST and adolescent interpersonal violence, future DMST prevention and intervention strategies focused on education should provide messaging and resources for violence beyond DMST, while screening and/or service provisions for adolescents should ask about and incorporate resources for interpersonal violence along with DMST.…”
Section: Discussionmentioning
confidence: 99%
“…Antitrafficking practice efforts should incorporate these findings to consider DMST as interconnected to other forms of violence, which can inform prevention and intervention efforts. In examining dynamics of DMST cases, Twis et al (2020) highlighted the similarities found between the context and dynamics of the DMST violence and the dynamics known to exist in adolescent IPV or teen dating violence situations. The findings presented here linking DMST and community violence, along with the noted similarities between trafficker-inflicted violence and adolescent partner violence, emphasizes the need to integrate DMST prevention efforts in advocacy and programing that target community violence and/or IPV in adolescence (Twis, 2020;Twis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could be because students focused on the part of the question that focused on trading for safety, which could overlap with teen dating violence. This finding is consistent with the previous studies that also found dating violence as a risk factor of minor sex trafficking (Countryman-Roswurm & Bolin, 2014;Twis, Gillespie, & Greenwood, 2020). Given the extant literature suggesting that some youth, particularly cisgender women/girls, are trafficked through an intimate partner (Lutnick, 2016), it is also possible that some youth who experience violence are trading sex in the context of an intimate relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the US on the secondary case files of 38 domestic minors sexually trafficked by their romantic partners between 2012 and 2017 found that traffickers frequently exercise sexual and psychological violence to control victims. Victims perceived traffickers as romantic partners or boyfriends before being sexually exploited (Twis et al, 2020a). Traffickers used the illusion of romance to groom victims and facilitate their recruitment, then escalated violence and manipulation.…”
Section: Influence Of Intimate Relationshipsmentioning
confidence: 99%